Medieval theory of authorship : scholastic literary attitudes in the later Middle Ages - Minnis, A. J. (Alastair J.) (Middle Ages series., 1988)
It has often been held that scholasticism destroyed the literary theory that was emerging during the twelfth-century Renaissance, and hence discussion of late medieval literary works has tended to derive its critical vocabulary from modern, not medieval, theory. In Medieval Theory of Authorship, now reissued with a new preface by the author, Alastair Minnis asks, "Is it not better to search again for a conceptual equipment which is at once historically valid and theoretically illuminating?"Minnis has found such writings in the glosses and commentaries on the authoritative Latin writers studied in schools and universities between 1100 and 1400. The prologues to these commentaries provide valuable insight into the medieval theory of authorship. Of special significance is scriptural exegesis, for medieval scholars found the Bible the most difficult text to describe appropriately and accurately